Sugarcoated isolation: evidence that social avoidance is linked to higher basal glucose levels and higher consumption of glucose - Ein-Dor, Tsachi; Coan, James A.; Reizer, Abira; Gross, Elizabeth B.; Dahan, Dana; Wegener, Meredyth A.; Carel, Rafael; Cloninger, Claude R.; Zohar, Ada H. (Frontiers in Psychology, 2015)
Objective: The human brain adjusts its level of effort in coping with various life stressors as a partial function of perceived access to social resources. We examined whether people who avoid social ties maintain a higher fasting basal level of glucose in their bloodstream, reflecting a strategy to draw more on personal resources when threatened. Methods: For Study 1, we obtained fasting blood glucose and adult attachment orientations data from 60 undergraduate women at the University of Virginia. For Study 2, we collected measures of fasting blood glucose, self-reported trait anxiety, DHEA-cortisol, hypertension, and adult attachment orientations from 285 older adults of mixed gender, using a measure of attachment style different from study 1. Results: In study 1, fasting blood glucose levels corresponded with higher attachment avoidance scores after statistically adjusting for interpersonal anxiety. For study 2, fasting blood glucose continued to correspond with higher adult attachment avoidance even after statistically adjusting for interpersonal anxiety, trait anxiety, DHEA-cortisol and hypertension. Conclusions: Results suggest socially avoidant individuals upwardly adjust their basal glucose levels with the expectation of increased personal effort because of limited access to social resources.